2021
DOI: 10.1186/s12888-021-03603-6
|View full text |Cite
|
Sign up to set email alerts
|

Inattention and hyperactivity symptoms in childhood predict physical activity in adolescence

Abstract: Background Physical activity has been documented to influence several aspects of physical and mental health. Growing evidence shows that physical activity can improve attention. Less is known about how symptoms of inattention and hyperactivity / impulsivity in childhood are associated with physical activity in adolescence. We aimed to explore this relationship further. Methods We used a cohort of 3949 Swedish children (1884 boys and 2065 girls) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
3
3
0
Order By: Relevance
“…Interestingly, we found that time spent on MVPA was positively associated with impulsivity. This is in line with several previous studies [ 49 , 50 ]. For instance, a longitudinal study on Swedish children showed that hyperactivity/impulsivity symptoms in childhood were associated with a higher likelihood of being physically active in adolescence, whereas the opposite was true for inattention [ 49 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Interestingly, we found that time spent on MVPA was positively associated with impulsivity. This is in line with several previous studies [ 49 , 50 ]. For instance, a longitudinal study on Swedish children showed that hyperactivity/impulsivity symptoms in childhood were associated with a higher likelihood of being physically active in adolescence, whereas the opposite was true for inattention [ 49 ].…”
Section: Discussionsupporting
confidence: 94%
“…This is in line with several previous studies [ 49 , 50 ]. For instance, a longitudinal study on Swedish children showed that hyperactivity/impulsivity symptoms in childhood were associated with a higher likelihood of being physically active in adolescence, whereas the opposite was true for inattention [ 49 ]. As the cross-sectional and observational nature of our study prevents causal inferences, these observed associations might indicate an effect of impulsivity on diet and other lifestyle factors, an effect of diet and other lifestyle factors on impulsivity, or both.…”
Section: Discussionsupporting
confidence: 94%
“…For instance, Khalife et al (2014) found that childhood ADHD-IN symptoms were prospectively associated with obesity via physical inactivity. Another study found ADHD-IN symptoms, but not ADHD-HI symptoms, to predict less physical activity in adolescence, after controlling for demographic factors (Selinus et al, 2021). Although the proposed mechanism linking ADHD and physical inactivity at the neurobiological level does not differentiate ADHD-IN and ADHD-HI symptoms given the proposed widespread impact on dopamine and norepinephrine release throughout the brain (including proposed differential regions underlying ADHD-IN and ADHD-HI symptoms; Chang et al, 2012; Wigal et al, 2013), the behavioral link between ADHD-IN and physical inactivity has been hypothesized to be related to executive functioning deficits that could be specific to ADHD-IN symptoms (e.g., difficulties with meta-cognitive awareness, difficulties with structure and organization that would be required within team-based sports; Khalife et al, 2014).…”
Section: Physical Activity In Adolescents With Adhdmentioning
confidence: 99%
“…Despite the extant literature documenting less physical activity in adolescents with ADHD, a major limitation is that the majority of these studies are drawn from population-based samples where ADHD is defined based solely on caregiver report that their child had been previously diagnosed with ADHD by a clinician (Kim et al, 2011; Tandon et al, 2019; Wang et al, 2022), and the measurement of physical activity includes one-item assessing exercise frequency (Kim et al, 2011; Selinus et al, 2021; Tandon et al, 2019; Wang et al, 2022). In order to augment our understanding of the nature of physical inactivity in adolescents with ADHD, it is important to utilize more comprehensively diagnosed samples and to examine the type (e.g., independent exercise, structured activities like sports participation), frequency (e.g., times each week), intensity (e.g., breathing hard), duration (e.g., 20-min, 60-min), and timing (e.g., after school, on weekends, in free time) of physical activity in adolescents diagnosed with ADHD.…”
Section: Physical Activity In Adolescents With Adhdmentioning
confidence: 99%
See 1 more Smart Citation